(3YScQjIs - (3CHh GdYR GdOjf GdMdHjs
(3ChdgG (B:s
(3HOCJ HGSe GdeHOY GdNdb hGdUhQ Edg Ydi cd GdNdjbI GbJOQ s
(3hgj bUjOg ai XghQ GdSjO GdYXje GdegOi GdefJXQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI JhHLf HCdeGfjG (B(237) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs